2019
DOI: 10.1002/cpt.1490
|View full text |Cite
|
Sign up to set email alerts
|

Using Healthcare Databases to Refine Understanding of Exploratory Associations Between Drugs and Progression of Open‐Angle Glaucoma

Abstract: We sought to refine understanding about associations identified in prior studies between angiotensin‐II receptor blockers, metformin, selective serotonin reuptake inhibitors, fibric‐acid derivatives, or calcium channel blockers and progression to glaucoma filtration surgery for open‐angle glaucoma (OAG). We used new‐initiator, active‐comparator cohort designs to investigate these drugs in two data sources. We adjusted for confounders using stabilized inverse‐probability‐of‐treatment weights and evaluated resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…[ 8 ] Previously, Wang et al . [ 4 ] have also reported similar findings. In their study, the administration of metformin did not halt the progression of POAG.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…[ 8 ] Previously, Wang et al . [ 4 ] have also reported similar findings. In their study, the administration of metformin did not halt the progression of POAG.…”
supporting
confidence: 65%
“…[ 2 ] Studies have hypothesized that metformin upregulates adenosine monophosphate-activated protein kinase (AMPK). [ 3 4 5 ] AMPK upregulation alters the tone of cells in the trabecular meshwork, thus lowering the IOP and preventing the progression of glaucoma. [ 6 7 ] Preliminary results from animal studies have also shown that metformin exerts neuroprotective effect by upregulation of AMPK.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…-группа американских ученых не выявила аналогичных протекторных эффектов метформина. Возможно, это связано с различиями в дизайне исследований, в частности вызывает определенные вопросы использование в качестве основного критерия прогрессирования ПОУГ во втором исследовании необходимость выполнения антиглаукомной операции [39].…”
Section: прочие кардиологические средстваunclassified
“…They studied ten years of data from the Clinformatics Data-Mart Database for diabetic individuals and reported that metformin is associated with a reduced risk of developing POAG in people with diabetes when taken above a threshold prescription amount of 1110 g.[ 5 ] Studies have also shown metformin not being associated with the reduced risk of progression of glaucoma. [ 6 ] We explored the possible association between metformin use and the incidence of glaucoma among individuals of Indian ethnicity using population-based cohort data from the Chennai Glaucoma Study and the Chennai Eye Disease Incidence Study.…”
mentioning
confidence: 99%